PENGARUH PENAMBAHAN EKSTRAK BAWANG PUTIH (Allium sativum) TERHADAP KARAKTERISIK EDIBLE FILM PATI GANYONG (Canna edulis Kerr.) - Ratna Paramitha Sari; Septia Tri Wulandari; Dyah Hesti Wardhani (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Canna starch (Canna edulis Kerr.) has a relatively high amylose content about 32.53% hence it could potentially be used as raw material of edible film. The addition of additives such as antimicrobials and antioxidants should improve the quality and ability of edible film to prevent damage to food materials. Garlic (Allium sativum) contains Allicin which is a strong antioxidant and antimicrobial agent. The purpose of this research is to study the effect of the addition and the optimal composition of garlic extract edible film characteristics. Independent variables in this study were the canna starch concentration (3% w / v) and sorbitol concentration ( 2% w / w). The addition of variables of extract garlic acid of 0%, 5%, 10% and 15% (v / v solution). Film characterizing in thickness, tensile strength and percent elongation ,and Scanning Electron Microscopy (SEM). The results of this study indicate that the addition of garlic extract affects the physical and mechanical characteristics of the edible film impairment tensile strength, percent elongation and increased thickness of the edible film. The best result observed at edible films with 5% concentration of garlic extract which has a value of 2.03 kgf/cm2 tensile strength, percent elongation of 20.62%, and thickness of 0.04 mm. Whereas the SEM analysis, surface edible films with 0% concentration of garlic extract looks more refined than the edible film with 5% concentration of garlic extract.